2021
DOI: 10.1159/000515952
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Aspects of Public Attitudes Toward Whole Genome Sequencing to Inform the Integration of Genomics into Care

Abstract: <b><i>Introduction:</i></b> The growth of global sequencing initiatives and commercial genomic test offerings suggests the public will increasingly be confronted with decisions about sequencing. Understanding public attitudes can assist efforts to integrate sequencing into care and inform the development of public education and outreach strategies. <b><i>Methods:</i></b> A 48-item online survey was advertised on Facebook in Eastern Canada and hosted on SurveyMonk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Current challenges facing geneticists include decisions on type of DNA sequencing appropriate for each clinical situation, and best choice of laboratory and facilities for data interpretation. Patient concerns of confidentiality and control over genomic data must also be investigated and addressed for integration into healthcare ( 46 , 47 ). Examples of genetic analysis linked to precision medicine are seen in the investigation of the multiple causes of short stature, including epigenetic defects, syndromic growth failure and the search for causative genetic variants of obesity of endocrine—either pro-opiomelanocortin (POMC) deficiency or leptin receptor (LEPR) deficiency obesity—or syndromic origin ( 17 , 41 , 45 , 48 52 ).…”
Section: Genomics In Precision Medicinementioning
confidence: 99%
“…Current challenges facing geneticists include decisions on type of DNA sequencing appropriate for each clinical situation, and best choice of laboratory and facilities for data interpretation. Patient concerns of confidentiality and control over genomic data must also be investigated and addressed for integration into healthcare ( 46 , 47 ). Examples of genetic analysis linked to precision medicine are seen in the investigation of the multiple causes of short stature, including epigenetic defects, syndromic growth failure and the search for causative genetic variants of obesity of endocrine—either pro-opiomelanocortin (POMC) deficiency or leptin receptor (LEPR) deficiency obesity—or syndromic origin ( 17 , 41 , 45 , 48 52 ).…”
Section: Genomics In Precision Medicinementioning
confidence: 99%
“…The attitude scale used in this study could be improved with additional questions about specific elements of genomic research and genetic testing, such as funding or social justice issues. Thus, there is a need, and a movement in current research, to develop and validate high-quality measures of genomic knowledge, attitudes, and behavior [49, 50]…”
Section: Discussionmentioning
confidence: 99%
“…The attitude scale used in this study could be improved with additional questions about specific elements of genomic research and genetic testing, such as funding or social justice issues. Thus, there is a need, and a movement in current research, to develop and validate high-quality measures of genomic knowledge, attitudes, and behavior [49,50] The originality of some of our measures of knowledge and behaviors may make interpretation more difficult. For example, we surveyed participants about behaviors they already performed as well as their intentions to perform them in the future.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Sixteen studies were included in the analysis [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Most were quantitative (n = 12), using questionnaires to assess public perceptions [46-52, 54, 56, 57, 59, 61].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The US has contributed the most to this field thus far, undertaking six of the 16 studies identified in the literature search [49,50,52,53,55,58]. This is followed by Canada (n = 2) [48,51] and Japan (n = 2) [54,59]. Each of the following countries contributed one study: Jordan [56], Korea [57], The Netherlands [61], Singapore [60], Qatar [46] and the UK [47].…”
Section: Study Characteristicsmentioning
confidence: 99%